Pembelajaran Al Quran Berbasis Hafalan Menggunakan Media E-Pen untuk Anak Usia Dini - Alwatasi, Umar; Salsabila, Unik Hanifah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
Education at this time can be done in various ways using increasingly advanced technological facilities. Today's technology can be used in various fields, including education. This is a demand for a teacher to improve learning methods for their students, so that students become more interested in learning. The purpose of this research will be to describe memorization-based learning of the Koran for early childhood using the e-pen tool. This article was compiled with the title Memorization-Based Al-Qur'an Learning Using E-Pen Media for Early Childhood. The method used in this article is literature study and interviews. The result is that memorizing with e-pen media makes it easy for children and parents. The success of memorizing in early childhood is the contribution or role of parents in accompanying children to play audio using an e-pen repeatedly and istiqomah.